2004
DOI: 10.1051/forest:2004017
|View full text |Cite
|
Sign up to set email alerts
|

Growth response to thinning in Quercus pyrenaica Willd. coppice stands in Spanish central mountain

Abstract: -This paper presents the growth response of coppice forest of Quercus pyrenaica Willd. to thinnings of different intensities. Four treatments were tested: light, moderate and heavy thinning with respectively 25, 35 and 50% of basal area removed, and no thinning (control). The results obtained show significant differences between treatments for diameter and biomass of the mean tree and for current diameter increment, for the three inventories carried out (1994, 1998, 2002). The largest values for the mean tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 16 publications
11
92
0
4
Order By: Relevance
“…In the case of pyrenean oak stands, the anthropogenic impact from villages located nearby takes the form of recurrent fires, livestock grazing, collection of firewood or poles as well as harvesting of non-timber products (Cañellas et al, 2004). In addition, the regeneration of pyrenean oak generally takes place through stump and/or root sprouting; so stand dynamics differ from those of others species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of pyrenean oak stands, the anthropogenic impact from villages located nearby takes the form of recurrent fires, livestock grazing, collection of firewood or poles as well as harvesting of non-timber products (Cañellas et al, 2004). In addition, the regeneration of pyrenean oak generally takes place through stump and/or root sprouting; so stand dynamics differ from those of others species.…”
Section: Discussionmentioning
confidence: 99%
“…The present model does not capture the U-shape, probably due to the low frequency of trees larger than 50 cm dbh in the data set (160 trees of 4 505 total, 3.5%). This stand structure is due to the management practices applied up to the middle of the last century in this kind of stands, which were managed as either coppices or coppices with standards, by cutting trees every 20 y with subsequent shoot or root regeneration (Cañellas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbour [4] suggested that thinning could accelerate the development of some features of stand structure found in late seral stage forests. The effects of thinning on yield, diameter distribution, height and diameter growth have been widely studied for coppices [5,6,9,17]. However, although studies have been carried out recently on Q. ilex [13] and Q. pubescens [15], changes in stand structure are not as well documented.…”
Section: F Montes Et Almentioning
confidence: 99%
“…Moreover, given the role of mountain forests as a defense against natural hazards and for preservation of high-quality water resources, biodiversity conservation and ecosystem services have become increasingly important in recent decades (Brunet et al 2010;Scarascia-Mugnozza et al 2000). These considerations supported widespread conversion of many beech coppices into high forests, as commonly observed in many European countries and forest tree species (Cañellas et al 2004;Di Matteo et al 2010;Van Calster et al 2007). This was motivated by a reputation of high forests as a provider of more productive and ecologically functional stands.…”
Section: Introductionmentioning
confidence: 99%